Static and dynamic combined effects on the thermal conductivity of water based Ironoxide Nanofluids: experiments and theories - Arifutzzaman, A.; Ismail, Ahmad Faris; Alam, Md. Zahangir; Khan, Ahsan Ali; Aslfattahi, Navid; Saidur, R. (Taylor and Francis Ltd., 2021)
Reasoning of particular mechanism of anomalous thermal transport behaviors is not identified yet for the nanofluids. In this research, the thermal conductivity of maghemite (MH) nanoparticles dispersed deionized water (DW) nanofluids (MH/DW) has been evaluated for the first time using the modified effective medium theories (EMTs). EMTs have been modified with the consideration of static and dynamic effects combinedly for the analysis of anomalous behaviors of thermal conductivity enhancements of the spherical nanoparticles dispersed nanofluids. MH nanoparticles (~20 nm) were synthesized using chemical co-precipitation techniques. MH/DW nanofluids were prepared with the varying MH nanoparticles loading in DW and thermal conductivity was measured using KD2 pro device. The thermal conductivity enhancement (~32 %) was found to be increased linearly with the increasing MH nanoparticle concentration and nonlinearly with the increasing temperature. Existing Maxwell and Maxwell Gantt EMA (MG-EMA) models exhibited awful under-prediction from experimental thermal conductivities of MH/DW nanofluids. Modified model with considering static and dynamic mechanisms of MH nanoparticles combinedly showed reasonably very good agreement with the experimental thermal conductivities of MH/DW nanofluids at elevated temperature. This modified model opens the new windows to analyze the insight of the thermophysical properties of various types of nanofluids by introducing potential parameters.